Exploring the Structural Transformation Mechanism of Chinese and Thailand Silk Fibroin Fibers and Formic-Acid Fabricated Silk Films - Liu, Qichun; Wang, Fang; Gu, Zhenggui; Ma, Qingyu; Hu, Xiao (International journal of molecular sciences, 2018)
Silk fibroin (SF) is a protein polymer derived from insects, which has unique mechanical properties and tunable biodegradation rate due to its variable structures. Here, the variability of structural, thermal, and mechanical properties of two domesticated silk films (Chinese and Thailand B. Mori) regenerated from formic acid solution, as well as their original fibers, were compared and investigated using dynamic mechanical analysis (DMA) and Fourier transform infrared spectrometry (FTIR). Four relaxation events appeared clearly during the temperature region of 25 °C to 280 °C in DMA curves, and their disorder degree (fdis) and glass transition temperature (Tg) were predicted using Group Interaction Modeling (GIM). Compared with Thai (Thailand) regenerated silks, Chin (Chinese) silks possess a lower Tg, higher fdis, and better elasticity and mechanical strength. As the calcium chloride content in the initial processing solvent increases (1%–6%), the Tg of the final SF samples gradually decrease, while their fdis increase. Besides, SF with more non-crystalline structures shows high plasticity. Two α- relaxations in the glass transition region of tan δ curve were identified due to the structural transition of silk protein. These findings provide a new perspective for the design of advanced protein biomaterials with different secondary structures, and facilitate a comprehensive understanding of the structure-property relationship of various biopolymers in the future.